EFFECTIVENESS OF YOUTUBE AS AN EDUCATIONAL TOOL FOR TEACHING ORTHODONTICS TO UNDERGRADUATE DENTAL STUDENTS - Shah, Syed Suleman; Brekhna Jameel,; Wasim Ijaz,; Naveed Iqbal,; Humera Adeeb,; Siyyar Ahmad, (Journal of Ayub Medical College Abbottabad, 2024)
Background: The advent of modern technology has dramatically influenced the availability of resources for students to learn and gain knowledge as well as improve their skills. Methods: Over six months, a randomized control trial (pretest-post-test design) was conducted at Khyber College of Dentistry, Peshawar. The aim was to compare the traditional method with YouTube learning to enhance students' diagnostic skills in lateral cephalometry and benefit the local dental community. Results: Seventy-four participants took part, with an average age of approximately 23 years having 35.1% male and 64.9% female participants. The control group's pre-test mean score was 5.54, significantly increasing to 13.62 in the post-test. The experimental group's pre-test mean score was 4.08, significantly rising to 15.29 in the post-test. The experimental group outperformed the control group in the post-test, with mean scores of 15.29 and 13.62, respectively. Participants showed overall satisfaction with course content, materials, instructor knowledge, and YouTube learning, though opinions on class location and equipment varied, with some expressing less satisfaction in this aspect. Conclusions: This current study signifies the use of YouTube as a teaching tool. YouTube based learning had a superior efficacy to traditional based learning for instruction of cephalometric landmarks identification.